2002
DOI: 10.1093/deafed/7.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Parental Stress in Mothers of Young Children With Hearing Loss

Abstract: This study examined parental stress in 184 hearing mothers of young children who are deaf or hard of hearing. Stress levels were measured in three domains using the short-form of the Parental Stress Index (PSI; Abidin, 1995). Mothers in this study demonstrated significantly less parental distress on the PSI than a normative, hearing group, although this difference was quite small. Differences between the hearing and hearing loss samples did not reach conventional levels of significance for the Dysfunctional Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
99
5
8

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 26 publications
12
99
5
8
Order By: Relevance
“…This finding is consistent with previous studies that have reported increased parental stress associated with lower child language ability, both among parents of deaf children in general (Chaffee, Cunningham, Secord-Gilbert, Elbard, & Richards, 1990;Pipp-Siegel et al, 2002) and among mothers of a child with an implant in particular (Zaidman-Zait & Most, 2005).…”
Section: Everyday Problems Stress and Child Characteristicssupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is consistent with previous studies that have reported increased parental stress associated with lower child language ability, both among parents of deaf children in general (Chaffee, Cunningham, Secord-Gilbert, Elbard, & Richards, 1990;Pipp-Siegel et al, 2002) and among mothers of a child with an implant in particular (Zaidman-Zait & Most, 2005).…”
Section: Everyday Problems Stress and Child Characteristicssupporting
confidence: 92%
“…Similar correlations also emerged in previous studies of stress among parents of children with hearing loss (e.g., Pipp-Siegel et al, 2002), which supported the decision to analyze parental stress subscales separately. In the current study, 16.1% (n ϭ 5) of parents scored at or above the clinical cutoff for the total PSI/SF score.…”
Section: Parental Stresssupporting
confidence: 84%
See 2 more Smart Citations
“…(Weisel et al, 2007: 55) Moreover, research on the relationship between CI and stress seems to suggest that the level of development in communicative behaviour on the child's part is related to the degree of stress for the parents (Weisel et al, 2007;Incesulu et al, 2003;Knussen & Sloper, 1992). This is especially the case when the child's development is slower than expected after implantation (Nicholas & Geers, 2003;Pipp-Siegel et al, 2002). The challenge of satisfactory communication also largely defines the implanted child's language development.…”
Section: Introductionmentioning
confidence: 99%